An Myh11 single lysine deletion causes aortic dissection by reducing aortic structural integrity and contractility - Keita Negishi; Kenichi Aizawa; Takayuki Shindo; Toru Suzuki; Takayuki Sakurai; Yuichiro Saito; Takuya Miyakawa; Masaru Tanokura; Yosky Kataoka; Mitsuyo Maeda; Shota Tomida; Hiroyuki Morita; et al. (Scientific Reports, 2022)
Abstract Pathogenic variants in myosin heavy chain (Myh11) cause familial thoracic aortic aneurysms and dissections (FTAAD). However, the underlying pathological mechanisms remain unclear because of a lack of animal models. In this study, we established a mouse model with Myh11 K1256del, the pathogenic variant we found previously in two FTAAD families. The Myh11 ∆K/∆K aorta showed increased wall thickness and ultrastructural abnormalities, including weakened cell adhesion. Notably, the Myh11 ∆K/+ mice developed aortic dissections and intramural haematomas when stimulated with angiotensin II. Mechanistically, integrin subunit alpha2 (Itga2) was downregulated in the Myh11 ∆K/∆K aortas, and the smooth muscle cell lineage cells that differentiated from Myh11 ∆K/∆K induced pluripotent stem cells. The contractility of the Myh11 ∆K/∆K aortas in response to phenylephrine was also reduced. These results imply that the suboptimal cell adhesion indicated by Itga2 downregulation causes a defect in the contraction of the aorta. Consequently, the defective contraction may increase the haemodynamic stress underlying the aortic dissections.